Mesoporous RF-Xerogels by Facile Hydrothermal Synthesis - Sakhon Ratchahat; Satoshi Kodama; Hidetoshi Sekiguchi; Wiwut Tanthapanichakoon; Khalid Al-Ali; Tawatchai Charinpanitkul; Apinan Soottitantawat; Apiluck Eiad-Ua; Kajornsak Faungnawakij (My University, 2015)
Mesoporous resorcinol-formaldehyde (RF) xerogels were difficult to obtain by conventional sol-gel polymerization at atmospheric pressure because the resulting tenuous RF-gel structures tended to shrink or collapse during subsequent hot-air drying.To avoid this problem, costly and energy-intensive supercritical drying and freeze-drying are often used.In this work the main goal was to produce high-quality RF xerogels with good mesoporosity and high surface area by employing a hydrothermal process.The hydrogel synthesis was carried out in an autoclave at elevated temperature and pressure in order to sufficiently strengthen its network structure.The initial reactant ratio was held constant to search for most suitable hydrothermal temperature and initial pH.The experimental results showed that the reaction in the autoclave at 140 ºC and initial pH of 6 could successfully produce RF xerogels with good mesoporosity (peaking pore radius rpeak = 2.38 nm), high specific surface area and large pore volume.The hydrothermal process was on the overall relatively simple, low-cost, and less time-consuming compared to the conventional atmospheric method.
Keywords: Hydrothermal Synthesis; Aerogels and thermal insulation